Strategi Pengembangan Istana Tambakbulusan Sebagai Destinasi Wisata Bahari di Kabupaten Demak - Fajar Setyo Rahmanto; Jasanta Peranginangin; Made Prasta Yostitia Pradipta (Jurnal Pariwisata Indonesia, 2020)
This skripsi examines the strategies or steps taken by the management of Istana Tambakbulusan in developing Istana Tambakbulusan as a marine tourism destination in Demak Regency. Including the constraints faced in the development process. The writing of this skripsi uses descriptive qualitative research to examine the strategy for developing Istana Tambakbulusan as a marine tourism destination in Demak Regency. The method of data collection is in-depth interviews with managers, in addition, other data is carried out by observation and field data. The data obtained were then analyzed qualitatively by data triangulation method and presented descriptively. The results of this study found that the strategy of developing attractions in the marine tourism destination of Istana Tambakbulusan will revive old activities or events that are no longer implemented, namely "rowing boat races". As well as physical development in the shoreline area (small scale reclamation) to accommodate more tourists. In addition, the development of amenity is to provide a proper place for UMKM to sell food, souvenirs, etc. Accessibility will continue to be carried out in accordance with the strategic plan for the development of the Istana Tambakbulusan. Meanwhile, in terms of ancillary service, coordination will be carried out with villagers to be willing to rent their houses for homestays, and will also add stakeholders, especially companies to provide CSR in fostering Tambakbulusan Village residents to develop ancillary services in the marine tourism area of Istana Tambakbulusan. The obstacle is the difficulty in educating the people of Tambakbulusan Village to be aware and care about tourism development in Tambakbulusan Village and with regard to budget constraints in development and constraints regarding cleanliness in the Istana Tambakbulusan tourist area.